2015
DOI: 10.1155/2015/213836
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Immune Response by Organophosphorus Pesticides: Fishes as a Potential Model in Immunotoxicology

Abstract: Immune response is modulated by different substances that are present in the environment. Nevertheless, some of these may cause an immunotoxic effect. In this paper, the effect of organophosphorus pesticides (frequent substances spilled in aquatic ecosystems) on the immune system of fishes and in immunotoxicology is reviewed. Furthermore, some cellular and molecular mechanisms that might be involved in immunoregulation mechanisms of organophosphorus pesticides are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 58 publications
2
20
0
9
Order By: Relevance
“…Increased level of nitric oxide under the influence of CPF may be attributed to that; fish body produces protective mechanism against the stress of pesticide. This result is in agreement with that obtained by Díaz-Resendiz et al [25] who reported increased production of nitric oxide significantly after exposure to pesticide. In addition, Xu et al [26] reported that CPF (1.16, 11.6 and 116 μg/L) induce an increase in the level of nitric oxide in C. carpio.…”
Section: The Chronic Toxicity Effect Of Chlorpyrifos On General Healtsupporting
confidence: 93%
See 1 more Smart Citation
“…Increased level of nitric oxide under the influence of CPF may be attributed to that; fish body produces protective mechanism against the stress of pesticide. This result is in agreement with that obtained by Díaz-Resendiz et al [25] who reported increased production of nitric oxide significantly after exposure to pesticide. In addition, Xu et al [26] reported that CPF (1.16, 11.6 and 116 μg/L) induce an increase in the level of nitric oxide in C. carpio.…”
Section: The Chronic Toxicity Effect Of Chlorpyrifos On General Healtsupporting
confidence: 93%
“…After 30 days, the lysozyme level was significantly increased in groups 2 and 3, while there were no significant differences in group 4 compared to the control group. The lysozyme is one of the humoral innate immune factors; which is considered as a natural antibiotic of fish [25]. O. niloticus exposed to CPF at a rate of 0.102 and 0.255 mg/L revealed an increase in the activity of lysozyme level; but the lower concentration (0.051 mg/mL) of such pesticide did not produce any change on the lysozyme activity [26].…”
Section: The Chronic Toxicity Effect Of Chlorpyrifos On General Healtmentioning
confidence: 99%
“…The molecular mechanisms by which OPs activate immune cells remain largely unknown. There is evidence that OPs trigger nonneuronal cholinergic signaling of inflammatory cells (90,144,220), and mechanisms involving activation of signaling pathways by OP metabolites as well as OP-induced cytotoxicity/cell death of immune cells have also been implicated (56).…”
Section: Inflammatory Mechanisms Of Op-induced Ahrmentioning
confidence: 99%
“…Sin embargo, existen más de 60 artículos derivados de investigaciones ecotoxicológicas recientes realizadas en México en peces (i.e. Martínez-Tabche et al 1994, Dzul-Caamal et al 2012, Díaz-Resendiz et al 2015, Sánchez-Garayzar et al 2016, Toledo-Ibarra et al 2016 (Anguiano et al 2007(Anguiano et al , 2010 e insectos (Valdovinos-Núñez et al 2009, Pérez-Cogollo et al 2015. Dichos estudios relacionan exposición de OC, OF, CA, PS y herbicidas, con efectos en la salud de organismos de prueba.…”
Section: Estudios Ecotoxicológicosunclassified